Mechanism of action of lncRNA-NEAT1 in immune diseases - Zhang, Ruo-Xuan; Zhang, Zi-Xuan; Zhao, Xiang-Yu; Liu, Yi-Han; Zhang, Xiao-Meng; Han, Qin; Wang, Xiao-Yu (Frontiers in Genetics, 2025)
NEAT1, a long non-coding RNA (lncRNA), is involved in assembling nuclear paraspeckles that have been found to impact various immune-related diseases, such as autoimmune diseases, allergic diseases, cancer immunity, sepsis, etc. In immune-related diseases, lncRNA-NEAT1 affects the activation, proliferation, and differentiation process of immune cells by interacting with transcription factors and miRNA (MicroRNA) to regulate an expression level in immune-related genes. It can also regulate the apoptosis and autophagy processes of immune cells by regulating inflammatory responses, interacting with apoptosis-related proteins, or regulating the expression of autophagy-related genes, thereby regulating the development of immune-related diseases. In recent years, a large number of researchers have found that the abnormal expression of lncRNA-NEAT1 has a great impact on the onset and progression of immune diseases, such as innate immunity after viral infection and the humoral immunity of T lymphocytes. In this paper, the specific mechanism of action and the function of lncRNA-NEAT1 in different immune-related diseases are sorted out and analyzed, to furnish a theoretical foundation for the study of the mechanism of action of immune cells.